The corrosion inhibition of (2Z,2′Z)-4,4′-(1,2-phenylene bis(azanediyl))bis(4-oxobut-2-enoic acid) for carbon steel in acidic media using DFT - K.M. Zohdy; A.M. El-Shamy; Atef Kalmouch; Elshafie A.M. Gad (Egyptian Journal of Petroleum)
A new synthesized sodium salt of [2Z,2′Z)-4,4′-(1,2-phenylene bis(azanediyl))bis(4-oxobut-2-enoic acid] (CI) is tested as corrosion inhibitor for carbon steel (CS) in 0.5 M H2SO4 solutions via electrochemical techniques. The results open circuit potential, potentiodynamic polarization and electrochemical impedance spectroscopy show that new compound has excellent inhibiting effect for CS corrosion in the corrosive sulfuric acid medium with efficiencies of approximately 99% at an optimum 150 ppm concentration. The results proved that the inhibitor is of a mixed cathodic/anodic type. Density function theory (DFT) is helpful in finding the relevancy of quantum chemical descriptors to the performance of this molecule as corrosion inhibitors. Some quantum descriptors such as EHOMO; energy of the highest occupied molecular orbital, ELUMO; energy of the lowest unoccupied molecular orbital, ΔE; the energy gap, η; Global hardness, S; global softness, I: ionization potential, A: electron affinity, X: absolute electronegativity, ω; global electrophilicity index, ΔEBack-donation; the back donation, f+, f; Fukui indices for local nucleophilic and electrophilic attacks were investigated. The feedback of descriptors calculation proves that the title molecule can perform as a corrosion inhibitor. Keywords: DFT, Quantum chemical descriptors, Fukui function, Local reactivity, Corrosion inhibition, Pickling solution